Representasi Unsur Misteri Dalam Poster Drama Light Shop: Kajian Semiotika Roland Barthes - Juvita Arsani; Christopher Yudha Erlangga; Yan Bastian (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
A drama series is a visual medium within the realm of nonverbal communication that represents various meanings through sociocultural conventions, particularly in the South Korean entertainment industry. One example is the poster for the drama Light Shop, which contains elements of mystery. This study aims to analyze the representation of mystery elements in the poster using Roland Barthes semiotic theory denotation, connotation, and myth. through a descriptive qualitative method with a constructivist approach. The results reveal that the Light Shop poster contains several visual signs that collectively create an atmosphere of mystery. In this poster, visual elements such as the dominant black and yellow colors symbolize death and enlightenment. In addition, the upward gaze symbol conveys a sense of hope, while the characters body postures symbolize anxiety and fear. The hanging lamp symbolizes the transitional line between life and death. The myth in the Light Shop poster represents the drama’s narrative that the hanging lamp emitting light can determine a person’s life or death. This study is expected to serve as a reference in the field of communication studies, particularly in visual semiotic analysis. In addition, this research can be applied as an implementation of Roland Barthes’ semiotic theory to analyze visual promotional media such as film posters. It is also expected to provide inspiration and new insights in the field of film poster design, especially in the use of visual elements containing symbolism to strengthen the visual communication message of the poster